Analisa dan Penerapan Activity Based Costing untuk Penentuan Harga Pokok Poduksi - Joni Hendra (Ecobuss, 2015)
The purpose of this research are (1) knowing the influence of activity based costing (abc) as an effort to produce calculation basic price the paper products hvs a more efficient and more accurate, (2) helping for ease in determine policy to determine the selling price paper hvs.This study adopted qualitative approaches descriptive with the approach case study.The subject of this research is PT.Suparma, tbkSurabaya.As for the period a financial report used were the reports on the production costs in january 2013 up to december 2013. Based on the research done can be concluded as follows (1) by using the method abc, so companies have basic price production more accurate.A comparison, basic price production in the paper products hvs 60 gsm roll in a traditional is higher ( overcosts compared with a method of abcnews.Basic price production overcosts indeed absorb the cost of smaller than traditional methods.While in the paper products hvs 60 gsmplano in a traditional lower ( undercosts compared with a method of abcnews.Hpp who undercosts indeed absorbs more greater than traditional methods.(2) the method of abc take more cost driver so that it will allocate overhead to each of product with more appropriate and accurately.Thus, through the use of a method of abc, distortion the cost of occurring can be removed or pressed minimum. While advice that can be assigned to this research is: (1) of the company need to repair in the calculation of the basic price production by not using the traditional systems / conventional again but by using activity based costing system. (2) before uses the abc should classifies a charge of friends The cost of energy and the cost of embalase to a group overhead to increase accuracy calculation basic price production (Keyword: activity based costing, overhead costæ, basic price production)